Überlegungen zum vermeintlichen Aufenthalt von Galla Placidia im Diokletianpalast in Split - Sanader, Mirjana (Acta Classica Universitatis Scientiarum Debreceniensis, 2024)
This paper has two objectives. Firstly, based on Philostorgius’ (HE XII,13) claims that the army of Theodosius II crossed Pannonia and Illyricum during the campaign in 424. against the usurper John. This unusually long route to Dalmatia will be examined and considered. In the scientific literature, information can sometimes be found that Galla Placidia had sojourned in the palace of the former Roman Emperor Diocletian in Split during the winter of 424/425. These data lead to the second goal of this paper, namely, to examine possible evidence for such an assertion.